Avaliação em Larga Escala: uma análise da diferença do rendimento do IDEB dos estudantes dos 5º anos comparados aos 9º anos do Ensino Fundamental em Língua Portuguesa - Matucheski, Vera Lúcia Panisson (2021)
This study analyzes the performance of the students in the 5th grade of Elementary Schools of the Municipal Education Network in the city of Cascavel, state of Paraná, and of students in the 9th grade of Elementary Schools in the state of Paraná’s Education Network, in Portuguese Language, in order to identify the factors that interfere directly or indirectly in the appropriation of the contents. The research is based on the quali-quantitative method by Creswell, and Bardin's Content Analysis. The analysis used official documents from the Ministry of Education, the National Institute of Educational Studies and Research Anísio Teixeira, the Brazilian Institute of Geography and Statistics, Portals: Academia QEdu, Todos pela Educação, Plataforma Scielo; theorists such as Sandra Zákia Souza, Alicia Bonamino, Flavia O. C. Werle, Valdecir Soligo among others. In addition to studies by the Center for Public Policies for the Evaluation of Education at the Federal University of Juiz de Fora, the Federal Constitution of 1988, the Law of Directives and Bases of Education of 1996, Decrees and Resolutions as a legal framework basis. The historical outline was defined from 1988 to 2019. For the analysis of the results, we used the IDEB and the contextual questionnaires of Prova Brasil of 2017 as a basis. The analysis carried out on the SAEB curricula and Reference Matrices found that : regarding the comparison of documents, Municipal Curriculum for Basic Education in Cascavel and the Curricular Guidelines for Basic Education in the state of Paraná, we find more similarities than differences, and in the comparison of these documents and the SAEB Reference Curriculum Matrices, the differences are more visible than the similarities, however, it did not allow us to infer a relationship between the documents and the academic performance of the research subjects. One of the categories analyzed based on the contextual questionnaires of Prova Brasil was the ―reading habits‖, which proved to be related to school performance in Portuguese, because the higher the student's reading habit indicator, the better the school performance measured.